ANALISIS DETERMINAN PROFITABILITAS PADAPERBANKAN KONVENSIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA - Tasya Aqilah, (2022)
Profitability is the ratio used to measure a company's ability to generate profits from its business activities. There are internal and external factors that can affect profitability in providing profits and losses to the company. The purpose of this study was to determine the effect of credit risk, liquidity, interest rates and inflation on the profitability of conventional banking in Indonesia. The population of this study is 47 commercial banks. The sampling technique used is a purposive sample technique with a total of 30 conventional banks listed on the Indonesia Stock Exchange (IDX) for the period 2017 - 2021. This study uses the Panel Data Regression Analysis technique as a hypothesis test by utilizing E-views 12 and a significance level of 5% (0.05). The results of this study are that credit risk has a significant effect on profitability, liquidity has no effect on profitability, interest rates have no effect on profitability, and inflation has a significant effect on profitability.